2018
DOI: 10.1002/asia.201800127
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Nitrogen‐doped Porous Carbons Derived from Metal‐Containing Ionic Liquids for Oxygen Reduction Reaction

Abstract: This study describes a self-doping and additive-free strategy for the synthesis of metal-nitrogen-doped porous carbon materials (CMs) via carbonizing well-tailored precursors, metal-containing ionic liquids (M-ILs). The organic skeleton in M-ILs serves as both carbon and nitrogen sources, while metal ions acts as porogen and metallic dopants. A high nitrogen content, appropriate content of metallic species and hierarchical porosity synergistically endow the resultant CMs (MIBA-M-T) as effective electrocatalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 59 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…ILs possess numerous merits, including reduced volatility, non-toxicity, a low vapor pressure, and high physico-chemical stability, which render them ideal candidates for the substitution of traditional volatile organic solvents and the sustainable synthesis of SMNCs [113][114][115][116]. It has been reported that the use of ILs as reaction media is highly efficient for the controllable synthesis of metal NPs of SMNCs, presenting several benefits [117][118][119][120]:…”
Section: Ionic Liquid-assisted Synthesismentioning
confidence: 99%
“…ILs possess numerous merits, including reduced volatility, non-toxicity, a low vapor pressure, and high physico-chemical stability, which render them ideal candidates for the substitution of traditional volatile organic solvents and the sustainable synthesis of SMNCs [113][114][115][116]. It has been reported that the use of ILs as reaction media is highly efficient for the controllable synthesis of metal NPs of SMNCs, presenting several benefits [117][118][119][120]:…”
Section: Ionic Liquid-assisted Synthesismentioning
confidence: 99%